Impacts of Total Physical Response on Young Learners’ Vocabulary Ability - Trung Cang, Nguyen; Diem, Le Thi Kieu; Thien, Le Quang (VNU Journal of Science: Education Research; Vol 37 No 4, 2021)
This study aimed to investigate the impacts of total physical response (TPR) method on the fourth graders’ vocabulary ability and their perceptions toward this method. This study was conducted at Luong The Vinh Primary school. There were 30 students participating in this study and they were divided into two groups: 15 students in experimental group (EG) and 15 students in control group (CG). The students in the experimental group were taught with TPR while students in the control one with grammar translation method. A mixed method was employed consisting of quantitative and qualitative approaches. Qualitative data were from the interviews to get feedback of students’ perception and advantages and disadvantages they faced when TPR was implemented in teaching vocabulary in their classroom. Quantitative data were from the questionnaire, scores of the pretest and posttest to check the impact of TPR on students’ vocabulary ability. The study revealed that the EG had better vocabulary learning ability than the CG. They not only remembered vocabulary better but also understood the meaning of the words more easily. It also showed that students had positive perceptions in learning vocabulary through TPR. In addition, the result from the interviews also revealed a limitation that it was sometimes not suitable especially for some outstanding students in the class. The results shed light on the impact of TPR on young learners’ vocabulary ability and perceptions toward TPR and provide some valuable features for further research studies that relate to TPR method in teaching vocabulary for young learners.